Endodontic Management of Teeth Juxtaposed to Haemangioma - Rekha Chandra Mani; Anchu Rachel Thomas; Premkumar Elavarasu; Vijay Venkatesh (Case Reports in Dentistry)
Vascular anomalies are localized defects in the vasculature that may or may not be present at birth. There are many types of vascular anomalies with different aetiology and clinical picture and, therefore, require the combined expertise of medical, radiological, and surgical specialities for its diagnosis and management. The term “haemangioma” is used as a common generic label to incorporate all types of vascular malformations. In this report, we describe a case of two maxillary premolars, requiring endodontic therapy, in close proximity to a haemangioma. The challenges encountered in the diagnosis and management of the case are discussed.